Pengaruh Citra Merek, Persepsi Harga Dan Lokasi Terhadap Keputusan Menginap Kembali (Studi Pada Konsumen Hotel Kriyad Arra Amandaru Cepu, Jawa Tengah) - Handrianto, Budi; Vildayanti, Rina Ayu; Noermijati; Aisjah, Siti; Ananda Sabil Hussein (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
The purpose of this study was to determine the effect of brand image, perceived price, and location on the decision to stay again. The sample in this study was 96 consumers from the Kyriad Arra Amandaru Cepu Hotel, Central Java, calculated using the Slovin Formula, with the method used being non-probability sampling by distributing questionnaires using the simple random sampling technique. The research instrument is a questionnaire with a Likert scale. The results of the respondents' answers to the questionnaire given were then processed using SPSS software version 25. The researchers found that the brand image variable partially affected the purchase decision variable, and the price perception and location variables had an effect on the decision variable to stay again.